Knowledge and Attitude of Pregnant Women Related to Hyperemesis Gravidarum at Jagong Health Center, Jagong Jeget District, Central Aceh Regency in 2021 - Dewi, Nova Ratna; Sri Wahyuni M.S.; Hidayana (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. Continuous hyperemesis gravidarum can cause a lack of food and fluids that can affect fetal development. Lack of food and fluids or dehydration has a bad effect on the unborn child as well as on the mother herself. This study aims to determine the extent of knowledge and attitudes of pregnant women to the incidence of hyperemesis gravidarum in the working area of the Jagong Health Center, Jagong Jeget District, Central Aceh Regency in 2021. Methods. This type of research is descriptive, the sample of this research is pregnant women in the working area of the Jagong Health Center totaling 30 people. Data were collected and measured using a questionnaire. Results. Mother's knowledge about hyperemesis gravidarum has a good level of knowledge as many as 15 respondents (50%), attitudes of pregnant women with hyperemesis gravidarum have a level of a positive attitude as much as 28 (80%), while knowledge of pregnant women and attitudes of pregnant women with hyperemesis gravidarum as much as 15 ( 50%). Conclusion. It is expected that pregnant women should be able to increase their knowledge and seek more information from health workers and media mass to increase the knowledge of pregnant women about health, especially regarding the incidence of hyperemesis gravidarum.